2015
DOI: 10.17093/aj.2015.3.2.5000145549
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phones As Distracting Tools In The Classroom: College Students Perspective

Abstract: There are more than six billion users of cell phones worldwide. The need for people to connect with others frequently is apparent in our society. People use mobile phones everywhere and every time, to call and text friends, surf the web, visit social sites and attach themselves to their communication devices at all times. As the use of mobile phones has proliferated in academic settings in recent years, new challenges are faced by institutions of higher education and their faculties. Research indicates that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
3
13
1
1
Order By: Relevance
“…The issue of students accessing social media platforms when a lecture is in session is not a new one. Ugur (2015), Olufadi (2015) and Hossain (2019) had similar findings in their studies. The implication is that students spend a considerable amount of time on their smartphones networking with friends and not necessarily for academic purposes.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The issue of students accessing social media platforms when a lecture is in session is not a new one. Ugur (2015), Olufadi (2015) and Hossain (2019) had similar findings in their studies. The implication is that students spend a considerable amount of time on their smartphones networking with friends and not necessarily for academic purposes.…”
Section: Discussionsupporting
confidence: 62%
“…Often the policy would state that students can use their mobile phones in class or in the library as long as they do not disturb the learning environment. Studies by Ugur (2015) and Fernandez (2018) show that the majority of participants were aware of guidelines restricting usage of mobile phones during classes. Ugur (2015) reported that authorities were considering banning use of mobile phones in the classroom.…”
Section: Policies On Mobile Phone Usage In the Classroom And Librarymentioning
confidence: 99%
See 2 more Smart Citations
“…Elde edilen bulgulara göre, ortaokul öğrencilerinde akıllı telefon bağımlılığının hem akademik başarıya hem de algılanan akademik başarıya göre manidar bir farklılık göstermediği saptanmıştır. Literatüre bakıldığında, yapılan çalışmalarda daha çok doğrudan akademik başarı dikkate alınırken sınırlı sayıda algılanan akademik başarının incelendiği araştırma olduğu göze çarpmaktadır (Bae, 2015;Dirik, 2016;Elmas, Kete, Hızlısoy ve Kumral, 2015;Kır ve Sulak, 2014;Lepp ve diğerleri, 2014;Martinotti ve diğerleri, 2010;Meral, 2017;Uğur ve Koç, 2015;Yıldırım, 2018;Young ve Case, 2004). Öğrencilerin akademik başarısında herhangi bir düşüş söz konusu olduğunda bunun kaynağının ne olduğunun iyi araştırılması büyük önem taşımaktadır.…”
Section: Tartışma Ve Sonuçunclassified